The Analysis of Illocutionary Types of Speech Acts in Yakin Nikah Web Series Season 1: Indonesian YouTube Short Film - Putu Claudia Suriani (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
In order to maintain a great means of communication between people, language use plays a significant role in the interaction process. Within the interaction process among speaker and hearer comes with an act or action along that is called speech acts, which refers to when a person is saying something, it is hoped that the hearer act as what the speaker intends him or her to do. Speech acts are always found in our daily basis, and even found in films, advertisements, and social media such as Instagram, Facebook, and YouTube. With the existence of YouTube, many short length films are found to have speech acts especially in one of the YouTube series entitled “Yakin Nikah”. By investigating “Yakin Nikah” characters’ speech acts, this research aims to explore the types of speech acts that exist and to analyse how those speech acts are then classified into Illocutionary act. This research uses descriptive qualitative method, by using several techniques such as visual analysis and textual analysis through watching the short film, writing down the transcriptions of the characters, identifying the written transcriptions into illocutionary act classifications. It is found that, the Directives speech acts are mostly present, followed by Representatives, Expressive, and last is Commissive with no signs of Declarative speech acts. In which it indicates that the Directives speech acts is present due to the speakers mostly wants the hearer to do something or respond to what the speaker has intended the speaker to do, Expressive acts to indicate the person’s state of psychology and last is the speech acts of future actions.